AKTIVITAS FOSFATASE TANAH DILINGKUNGAN BENTANG HUTAN ALAMI DAN NON-ALAMI - Suliasih, Suliasih; Rahmansyah, Maman (Research Center for Biology-Indonesian Institute of Sciences, 2009)
The spatial dispersal of acid and alkaline phosphates activity in forest soils appears to be controlled by position in the landscape and its soil microbial density. Soil bacteria expressively produced significant level of acid phosphatase in the investigation.The variety of acid phosphatase activity (8.25-37.55 />-nitrophenol.g